Modernisasi Beragama : Antara Tradisi dan Transformasi Sosial - Muhammad Iskandar Dalimunthe (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
Modernization, a global phenomenon, significantly impacts religious life, challenging religions to maintain their relevance amidst rapid social changes. This study aims to examine how religion, particularly Islam, can transform without losing its traditional essence, and to map the dynamics between tradition and modernity in religious practice. Employing a qualitative descriptive approach and library research methods, data were collected through literature review and analyzed thematically.The findings reveal a tension between tradition, perceived as a sacred heritage, and modernity, often suspected of introducing secular values. However, modernization also offers opportunities for religion to adapt through innovative outreach and reinterpretation of teachings. It is found that reinterpretation of religious teachings is crucial for contextual relevance, refreshing the understanding of universal values without altering the core doctrines. Furthermore, religion is not merely an object of modernization but also a vital actor in driving just social transformation, serving as a corrective force and an agent for civilizational development.In conclusion, religious modernization is an interactive process demanding responses from religious communities. The reinterpretation of doctrines is key to religion's ongoing relevance, and the synergy between tradition and transformation allows religion to remain pertinent and a moral guide in the globalized era.